Nests and nesting sites of Brazilian forest rodents (Nectomys squamipes and Oryzomys intermedius) as revealed by a spool-and-line device - Briani, D. C.; Vieira, E. M.; Vieira, M. V. (Polish Acad Sciences, 2001)
Patterns of nest construction and nest site selection of two murid rodents of the Brazilian Atlantic rainforest were described. The animals were captured in an area of about 1.5 ha of primary forest, marked, equipped with a spool-and-line device and released at the capture point. The next day we followed the thread to find their nests. In total 11 nests of Nectomys squamipes (Brants, 1827) and 13 of Oryzomys intermedius (Leche, 1886) were found. They were all egg-shaped, about 15 cm long and 10 cm wide, without any apparent entrance and consisted of dry leaves and grass. The two species differed in the selection of nest sites. The nests of N. squamipes were close to streams and built inside decomposed fallen logs or using natural entrances between the soil and tangled roots or rocky crevices. Nests of O. intermedius were built under or inside fallen logs and inside aerial root systems of palms. The spool-and-line technique used here is useful to provide detailed information on several aspects of the ecology and natural history of small mammals.
Keywords: Nectomys squamipes; Oryzomys intermedius; nests; rodents; spool-and-line device